Ascidians of the genus Aplidium collected on shallow hard-bottom reefs of coastal Georgia (Atlantic coast of N America, U.S.A.) - Sanamyan, Karen; Gleason, Daniel F. (Zootaxa, 2009)
Four shallow-water species of colonial ascidians of the genus Aplidium are identified in the collections made by divers off the coast of Georgia, U.S.A. One of the specimens, Aplidium ruzickai n. sp., is characterized by a combination of high numbers of rows of stigmata and stomach folds and is described as a new species.